Green Synthesis of ZnO Nanoparticles Using Diverse Plant Extracts: Sintesis Hijau Nanopartikel ZnO Menggunakan Ekstrak Tumbuhan yang Beragam - Abeer M. Muslim; Abeer H. Fezaa; Iqbal S. Naji (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Nanotechnology has emerged as a vital field for the development of functional materials at the nanoscale, with zinc oxide nanoparticles (ZnO NPs) gaining attention due to their high thermal stability, cost-efficiency, and antimicrobial properties. Specific background: Traditional physical and chemical synthesis methods, while effective, often pose environmental risks and scalability challenges. In contrast, green synthesis utilizing plant extracts offers a sustainable alternative. Knowledge gap: Despite growing interest, a comprehensive understanding of how different plant species and zinc salts affect ZnO NP morphology and functionality remains limited. Aims: This review aims to consolidate recent studies on the green synthesis of ZnO NPs using diverse plant extracts and zinc precursors, focusing on synthesis parameters and resulting nanoparticle characteristics. Results: Analysis reveals that variables such as molarity, temperature, and reaction time significantly influence particle size (8–66 nm), shape (spherical, hexagonal, rod-like), and bioactivity (antibacterial, anticancer, antioxidant). Novelty: This work systematically compares a wide array of plant-mediated synthesis strategies, offering a unique reference for optimizing ZnO NP production. Implications: These findings highlight the potential of eco-friendly synthesis routes for biomedical, environmental, and industrial applications, supporting further advancement in sustainable nanotechnology.Highlight : The review emphasizes the eco-friendly and cost-effective green synthesis of ZnO nanoparticles using various plant extracts. It discusses how synthesis conditions (e.g., temperature, molarity, reaction time) significantly affect size and morphology of ZnO NPs. Biosynthesized ZnO NPs exhibit diverse biomedical and environmental applications, including antimicrobial, anticancer, and photocatalytic uses. Keywords : Nanotechnology, Green Synthesis, ZnO Nanoparticles, Plant Extracts, Biomedical Applications